2005
DOI: 10.1016/j.asr.2005.03.144
|View full text |Cite
|
Sign up to set email alerts
|

The magnetosphere as a complex system

Abstract: The magnetosphere is a complex system, with multi-scale spatio-temporal behavior. Self-organization is a possible solution to two seemingly contradicting observations: (a) the repeatable and coherent substorm phenomena, and, (b) the underlying selfsimilar turbulent behavior in the plasma sheet. Such states, are seen to emerge naturally in a plasma physics model with sporadic dissipation, through spatio-temporal chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…In particular, it has been suggested that various magnetized plasma systems are in a self-organized critical state, exhibiting fractal and multifractal features which relate them to a broader class of complex systems. This has been the case in studies on the Earth's magnetosphere (Chang, 1999;Valdivia et al, 2005Valdivia et al, , 2003Valdivia et al, , 2006Valdivia et al, , 2013, the solar wind (Macek, 2010), the solar photosphere, and solar corona (Berger and Asgari-Targhi, 2009;Dimitropoulou et al, 2009). Some authors have discussed the relationship between the fractal dimension and physical processes in magnetized plasmas in the Sun-Earth system, including the possibility of forecasting geomagnetic activity (Aschwanden and Aschwanden, 2008;Uritsky et al, 2006;Georgoulis, 2012;McAteer et al, 2005McAteer et al, , 2010Dimitropoulou et al, 2009;Conlon et al, 2008;Chapman et al, 2008;Kiyani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that various magnetized plasma systems are in a self-organized critical state, exhibiting fractal and multifractal features which relate them to a broader class of complex systems. This has been the case in studies on the Earth's magnetosphere (Chang, 1999;Valdivia et al, 2005Valdivia et al, , 2003Valdivia et al, , 2006Valdivia et al, , 2013, the solar wind (Macek, 2010), the solar photosphere, and solar corona (Berger and Asgari-Targhi, 2009;Dimitropoulou et al, 2009). Some authors have discussed the relationship between the fractal dimension and physical processes in magnetized plasmas in the Sun-Earth system, including the possibility of forecasting geomagnetic activity (Aschwanden and Aschwanden, 2008;Uritsky et al, 2006;Georgoulis, 2012;McAteer et al, 2005McAteer et al, , 2010Dimitropoulou et al, 2009;Conlon et al, 2008;Chapman et al, 2008;Kiyani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At this location, the actions of X-ray, ultraviolet, and another wavelengths from the Sun are 132 M. J. A. Bolzan et al: Multifractal analysis of VTEC at equatorial region and low latitude more direct, strong, and constant throughout the year, compared with SJC, which is situated at 23 • S. This fact could explain the higher values found for the µ parameter for Belém compared with SJC, even though the last site is near IEA peaks (Walker, 1981;Walker and Strickland, 1981).…”
Section: Discussionmentioning
confidence: 54%
“…The SJC site is near −20 • (−23 • in fact) and would have strong influence from the IEA, resulting in higher values of the µ parameter compared to the Belém site. However, it is important to mention that we analysed data sets obtained from low solar activity periods, 2006 and 2007, and the IEA would not be strong compared with high solar activity period, as studied by Walker (1981) and Walker and Strickland (1981). This fact could explain the higher values found for the µ parameter for Belém compared with SJC, even though the last site is near IEA peaks.…”
Section: Results and Interpretationmentioning
confidence: 83%
See 2 more Smart Citations